The mediating role of dynamic managerial capabilities: The interplay between dominant logic and small‐ and medium‐sized enterprises performance in China. Issue 2 (14th August 2019) - Khan, Kashif Ullah; Atlas, Fouzia; Xuehe, Zhang; Khan, Farhan; Khan, Shabnam
Abstract : Transition economies, such as China, are characterized by volatile and rapidly changing markets. Firms, in order to be successful and get a competitive advantage over their competitors, need to build intangible resources. In the light of the resource‐based view and dominant logic (DL), this study is an endeavor in this regard and proposes that DL and managerial capabilities are intangible resources, which can drive the performance of small‐ and medium‐sized enterprises (SMEs). We hypothesized that dynamic managerial capabilities (DMCs), measured by human capital along with social capital and managerial cognition, play a mediating role in the relationship between DL, consisting of proactiveness and routine, and firm performance. The data in this study were obtained through a survey from 204 SMEs in China and were analyzed by structural equation modeling to generate results. We found that while successfully utilizing intangible/operant resources that are characterized as firm dynamic capabilities, SMEs can achieve superior performance and competitive advantage. Our results support the proposed hypotheses that show the importance and significance of DL and DMCs in order to attain higher level of performance. The concept of DL and its impact on SME's performance has been less researched in general, particularly in China. Limited research is available regarding intangible resources and their impact on SME performance in China.